Coral Reef Science Strategy for Ecosystem Symbiosis and Coexistence with Humans under Multiple Stresses - Kayanne, Hajime (Coral Reefs of the World,, 2016)
This book aims to illuminate coral reefs which comprise a symbiotic system coexisting among ecosystems, landforms, and humans at various levels and to provide a scientific basis for its reconstruction. The authors conducted an interdisciplinary project called "Coral Reef Science" from 2008 to 2012 and obtained novel results and clues to unite different disciplines for a coral reef as a key ecosystem.